Three new sequences of Ostrea stentina and the evolution of the mitogenome of the Ostreinae clams (Ostreidae, Bivalvia) - Corrain, Daniele; Franch, Rafaella; Babbucci, Massimiliano; Tagliapietra, Davide; Guarneri, Irene; Sigovini, Marco; Bonfatti, Valentina; Patarnello, Tomaso; Negrisolo, Enrico (Frontiers in Marine Science, 2025)
Oysters are a group of bivalves forming the family Ostreidae. The identification of oysters at species level is sometimes difficult. The use of molecular data has drastically improved the reliability of species identification and our understanding of their phylogenetic relationships. Markers obtained from mitochondrial genome have played and continue to play a key role in this process. Complete mitogenomes are still unavailable for many oyster species. We sequenced three complete mitogenomes of the dwarf oyster Ostrea stentina. We performed a comparative and evolutionary mitogenomic study of the new sequences combined with all available ones for the Ostreinae. The mitogenome of O. stentina exhibited the standard gene order of Ostreinae, which is different from those observed in other subfamilies of Ostreidae. The study of these mitogenomic arrangements identified gene blocks that were present in the mitogenome of the last common ancestor of the Ostreidae. The comparative analysis allowed identifying peculiar features of the mitogenomes of Ostreinae as well as of their protein coding genes, tRNAs genes, rRNA genes, and control regions. The genus Ostrea resulted polyphyletic in the mito-phylogenomic analysis. The stems and loops of several tRNAs contained short DNA motifs useful to identify single species/groups of species. Short sequences, playing the role of molecular signatures characterizing a single taxon or a group of species, were identified also in the intergenic spacers. The identification of these taxonomic and phylogenetic markers reinforces the crucial role of mitogenomes in elucidating the evolutionary history of oysters.